Multiple Orientia clusters and Th1-skewed chemokine profile: a cross-sectional study in patients with scrub typhus from Nepal. (March 2023) - Münch, Carina Chan-Song; Upadhaya, Bishnu Prashad; Rayamajhee, Binod; Adhikari, Anurag; Münch, Manuel; En-Nosse, Nora; Kowalski, Katharina; Eickmann, Markus; Bauer, Christian; Manandhar, Krishna Das; Keller, Christian
Highlights: There is high genetic variability of human-pathogenic Orientia tsutsugamushi strains from Nepal. We report the detection of seven distinct Nepalese Orientia clusters. Interleukin (IL)-6, IL-10, interferon-γ, and C-X-C motif chemokine ligand 10 in serum, but not tumor necrosis factor-α, correlate with bacteremia. We found an impaired Th2 response and a Th1-skewed chemokine profile in acute scrub typhus. Abstract: Objectives: Scrub typhus is an emerging infectious disease in Asia caused by Orientia tsutsugamushi ( Ot ). From Nepal, only scant data on the genetic epidemiology of this agent is available, and determinants of immunoregulation are poorly understood. Methods: Patients (n = 238) referred to the National Public Health Laboratory (Kathmandu, Nepal) from all over Nepal for suspected scrub typhus were enrolled upon positive immunoglobulin (Ig)M testing between July and October 2015. From Ot 16S and 47 kD polymerase chain reaction (PCR)-positive samples, the variable domain I of the 56 kD gene was sequenced and phylogenetically analyzed. T helper (Th) cell-associated cytokines (n = 13) and chemokines (n = 12) were quantified by multiplex bead arrays. Results: In 93/238 (39.1%) IgM-positive samples, Ot DNA was detected by quantitative PCR. Phylogenetic analysis of 56 kD sequences revealed seven distinct clusters, six of them with high homologies to strains detected in other countries. The Th1-related cytokines interferon-γ and C-X-C motif chemokine ligand 10 were strongly upregulated and correlated with bacteremia, while levels of Th2-associated chemokines were reduced. Bacteremia also correlated with concentrations of interleukin (IL)-6 and IL-10 but not tumor necrosis factor-α. Conclusion: We identified a considerable genetic heterogeneity of human-pathogenic Ot strains circulating in Nepal. Acute Nepalese scrub typhus patients showed strong Th1 but impaired Th2 responses, especially on the chemokine level.